Correction note to "on maximal (k,t)-sets" - Gulati, B.R. (Annals of the Institute of Statistical Mathematics, 1971)
Keywords: dept.mat

A study of H-spaces via left translations - Nowlan, R.A. (Pacific Journal of Mathematics, 1971)
H-spaces are examined by studying left translations, actions and a homotopy version of left translations to be called homolations. If (F, m) is an H-space, the map s: F-→FF given by s(x) = Lx, i.e. s(x) is left translation by x, is a homomorphism if and only if m is associative. In general, s is an An-map if and only if (F, m) is an An+1 space. The action r: FF × F → F is given by r(φ, x) = φ(x). The map s respects the action only of left translations. In general, s respects the action of homolations up to higherorder homotopies. Each homolation generates a family of maps to be called a homolation family. Denoting the set of all homolation families by H∞(F), s: F -→ FF factors through F → H∞(F) and this latter map is a homotopy equivalence. © 1971 Pacific Journal of Mathematics.
Keywords: dept.mat

On maximal (k,t)-sets - Gulati, Bodh Raj (Annals of the Institute of Statistical Mathematics, 1971)
This investigation was originally motivated by the problem of determining the maximum number of points in finite n-dimensional projective space PG(n, s) based on the Galois field GF(s) of order s=ph (where p and h are positive integers and p is the prime characteristic of the field), such that no t of these chosen points are linearly dependent. A set of k distinct points in PG(n, s), no t linearly dependent, is called a (k, t)-set for k1 >k. The maximum value of k is denoted by mt (n+1, s). The purpose of this paper is to find new upper bounds for some values of n, s and t. These bounds are of importance in the experimental design and information theory problems. © 1971 Institute of Statistical Mathematics.
Keywords: dept.mat

Orthogonal arrays of strength five - Gulati, Bodh Raj (Trabajos De Estadistica Y De Investigacion Operativa, 1971)
Keywords: dept.mat